A Visual Analysis of Multicultural in English Textbook for Elementary School - Dwi, Nur Laili; Huwaida, Adella Afifa; Unsyi, Rima Salsabila (JEdu: Journal of English Education, 2024)
Every teaching and learning activity needs an important component, namely Textbooks. So, the students need the best Textbook as their main learning material. The textbook's author additionally has to adapt the subject matter and substance to account for children's cognitive development at the appropriate age and stage of development. Children's visual perception can be impacted by the unique features of semiotic images, one of which comes from books that should be balanced with character teaching. One can study or research semiotic elements in textbook illustrations. My Next Word, class IV in an elementary school textbook, has been selected as the sample for this study's visual analysis of multiculturalism in Elementary School Textbooks. Utilizing qualitative research techniques, information and illustrations in the textbook were collected. Using Barthes' 1977 visual semiotic theory.